Therapeutic efficacy of a human papillomavirus type 16 E7 bacterial exotoxin fusion protein adjuvanted with CpG or GPI-0100 in a preclinical mouse model for HPV-associated disease. Issue 22 (16th May 2019) - Da Silva, Diane M.; Skeate, Joseph G.; Chavez-Juan, Elena; Lühen, Kim P.; Wu, Jiun-Ming; Wu, Chia-Mao; Kast, W. Martin; Hwang, KinKai
Abstract: Persistent human papillomavirus (HPV) infection is causally linked to the development of several human cancers, including cervical, vulvar, vaginal, anal, penile, and oropharyngeal cancers. To address the need for a therapeutic vaccine against HPV-associated diseases, here we test and compare the immunogenicity and therapeutic efficacy of a bacterial exotoxin fusion protein covalently linked to the HPV16 E7 oncoprotein adjuvanted with CpG or GPI-0100 in the C3.43 preclinical HPV16-transformed tumor model. We show that TVGV-1 protein vaccine adjuvanted with either CpG or GPI-0100 adjuvant induces a high frequency of E7-specific CD8 + T cells, and both adjuvants are able to assist the immune response in inducing polyfunctional cytokine-secreting lytic T cells that show therapeutic efficacy against well-established C3.43 tumors. CpG-adjuvanted TVGV-1 resulted in higher frequencies of IFNγ secreting and degranulating E7-specific T cells compared to GPI-0100-adjuvanted TVGV-1, resulting in marginally increased in vivo efficacy. Despite minor differences in immune response outcomes, we consider both CpG ODN and GPI-0100 to be promising vaccine adjuvants to increase the immunogenicity and therapeutic efficacy of the TVGV-1 protein for HPV16-driven cancers.